2022
DOI: 10.1039/d2tc00327a
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-sized polycrystalline diamond photodetector planar arrays for solar-blind imaging

Abstract: A high-quality 2-inch polycrystalline diamond was prepared by MPCVD technique. Photodetector planar arrays were then fabricated from the polycrystalline diamond. Clear solar-blind images have been obtained using the arrays as the sensing unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…c) State‐of‐the‐art PDCR and dark current properties for a variety of diamond photodetectors. [ 31–55 ] The dashed purple line represents metal‐semiconductor‐metal structure detectors. The solid blue line represents nanoparticle technology on diamond detectors.…”
Section: Resultsmentioning
confidence: 99%
“…c) State‐of‐the‐art PDCR and dark current properties for a variety of diamond photodetectors. [ 31–55 ] The dashed purple line represents metal‐semiconductor‐metal structure detectors. The solid blue line represents nanoparticle technology on diamond detectors.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, various studies have reported DUV PDs using UWBG materials such as Ga 2 O 3 , [17][18][19] Mg x Zn 1-x O, [20][21][22] Al 1-x Sn x O, [23] III-nitrides (Al x Ga 1-x N, [24][25][26] AlN, [27][28][29] and BN [30][31][32] ), and diamond. [33][34][35] The high crystalline UWBG semiconductors provide the narrowband photo response based on bulk charge generation through the incident wavelength near optical bandgap. [36] In the case of the ternary UWBG semiconductors such as Mg x Zn 1-x O, Al 1-x Sn x O, Al x Ga 1-x N, and Zn 1-x Ga x O, [37] they have exhibited great potentials in the viewpoints of the band state modulation controlled by the inter-doping content.…”
Section: Introductionmentioning
confidence: 99%
“…Solar-blind deep-ultraviolet (DUV) light, which is characterized by a wavelength range of 200–280 nm, is absent at the Earth’s surface due to its absorption by ozone and the atmospheric layer. , Photodetectors that can operate within this wavelength range are known as solar-blind photodetectors (SBPDs) . These photodetectors have the ability to detect solar-blind light without interference from natural ambient light, making them valuable in both military and civil applications, such as missile guidance, intersatellite communication, flame detection, biochemical analysis, remote control, and more. The development of wide-bandgap semiconductors like MgZnO, Al x Ga 1– x N, Ga 2 O 3 , and diamond has sparked significant research interest in SBPDs. These materials possess excellent radiation hardness, high thermal and chemical stability, and selective absorption in the solar-blind region.…”
mentioning
confidence: 99%